Hunger affects cleaning, signalling and signal reliability in the cleaner shrimp Ancylomenes pedersoni - Miya L. Ball; Benjamin M. Titus; Dan A. Exton; Eleanor M. Caves (Animal Behaviour, 2026)

Deeper Caribbean reef fish communities show greater taxonomic and functional change in dominance structure over a nine-year period - James S. Boon; Sally A. Keith; Dan A. Exton; Erika Gress; Dominic A. Andradi-Brown; Richard Field (Coral Reefs, 2026)
Fish communities at greater depths on a reef are thought to be less affected by disturbances that more strongly impact shallower areas. As a result, these deeper communities might be expected to show less change in their diversity and composition over time compared to those in shallow water. To test this hypothesis, we analysed changes in reef fish composition at 5-15 m and 25-40 m on reefs around Utila, Honduras, across two time periods: 2014-2015 and 2022-2023. We estimated taxonomic and functional α- and β- diversity using coverage-based standardisation and Hill-Chao numbers at orders q = 0 (species richness) and q = 2 (inverse Simpson index). Results showed that the α-diversity of fish communities was more consistent at 25-40 m than at shallower depths between the two time periods. However, β-diversity of dominant species and traits (q = 2) increased at greater depths, indicating that deeper fish communities became more distinct from one another in both structure and function, as well as more different from shallower communities at the same sites. Changes in diversity also varied between sites, highlighting the role of sitespecific conditions in shaping and maintaining fish communities across depths. Overall, the findings are not consistent with the expectation that greater depth reduces temporal community variability, and they raise questions about whether depth alone can serve as a refuge for reef fish.

Mangrove-based carbon market projects: Current trends and future perspectives - Jorge F. Montenegro; Midhun Mohan; Ewane Basil Ewane; Daniel A. Friess; Pandi P. Selvam; Abhilash Dutta Roy; Aaron Althauser; Jacob Tidwell; Julieta Gamboa-Cutz; Caileigh Shoot; Michael S. Watt; Peter I. Macreadie; et al. (Forest Policy and Economics, 2025)

Familiarity mediated by body size predicts intraspecific aggression in farming damselfishes - Catherine E. Sheppard; Lisa Boström-Einarsson; Dan A. Exton; Gareth J. Williams; Sally A. Keith (Behavioral Ecology and Sociobiology, 2025)
Aggressive territoriality can have significant benefits for resource acquisition yet is a costly behaviour. Selection should therefore favour mechanisms that allow individuals to modify their behaviour to maintain and defend their territory whilst minimising costs. One such mechanism between intraspecific territorial competitors is neighbour-stranger discrimination. The familiarity hypothesis suggests that territory holders will respond less aggressively to neighbours they recognise than to strangers they do not recognise. Conversely, in systems where neighbours pose a greater threat to territory loss than strangers, the threat-level hypothesis predicts that neighbours will elicit a greater aggressive response. We tested these opposing hypotheses in territorial farming damselfishes Stegastes diencaeus using a common bottle presentation experiment design to initiate aggressive responses by territory holders to neighbouring and non-neighbour individuals. Neighbours that were smaller in body size than the territory holder elicited the greatest aggressive response, whereas larger neighbours elicited the weakest. The aggressive response elicited by non-neighbours did not vary greatly with body size difference between the stimulus fish and territory holder. We demonstrate that aggressive response in territorial farming damselfishes is influenced by both familiarity and potential threat determined by body size. These findings add to the growing pool of evidence that an understanding of multiple factors is needed to identify the drivers of neighbour-stranger discrimination. Significance statement Both familiarity and body size may mediate aggressive behaviour yet are not often included in the same study. Using manipulative field experiments, we investigated the interplay between familiarity and body size in shaping patterns of aggressive behaviour in farming damselfishes. We found that territory holders were less aggressive towards neighbours than non-neighbours, but only when they were larger than themselves. Our results showing an interaction between the effects of familiarity and body size on aggressive behaviour may hint at nuances in patterns of neighbour-stranger discrimination, such as dominance relationships.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

The role of refuges in biological invasions: A systematic review - James S. Boon; Sally A. Keith; Dan A. Exton; Richard Field (Global Ecology and Biogeography, 2023)
Aim Ecological refuges buffer organisms against stressors and mediate a range of species interactions. However, their role in the context of biological invasions has yet to be synthesized, despite the increasing prevalence and impact of non‐native species. To address this, we conducted a systematic review aiming to determine the extent to which refuges are considered explicitly in the invasion literature and to synthesize their function. Location Global. Time period Present day. Major taxa studied All. Methods Our search of the literature was conducted using the SCOPUS and Web of Science databases and followed the preferred reporting items for systematic reviews and meta‐analyses (PRISMA) protocol. We obtained 315 records of refuge use in biological invasions from 300 studies. From each record, we extracted information relating to the experimental design, species characteristics and refuge type, where available. Results Refuges and refuge‐mediated processes are widely reported in the invasion literature. Native species commonly use refuges to avoid non‐native predation and competition, with spatial complexity and habitat heterogeneity key factors in facilitating their coexistence. Records show that artificial structures safeguard non‐natives in their introduced range. However, there were key differences in the use of such structures in marine and terrestrial environments. Moreover, the enhanced structural complexity created by non‐native plants and bivalves is often reported to act as a predation refuge for other species. Main conclusions The ubiquity of refuge‐based processes suggests that refuges can play an important role in affecting the persistence, spread and impacts of non‐native species, either through previously described mechanisms (i.e. refuge‐mediated apparent competition and the persistent pressure scenario) or through a mechanism we describe (i.e. when non‐native species use existing refuges), or both.

SCUBA noise alters community structure and cooperation at Pederson’s cleaner shrimp cleaning stations - Kieran P. McCloskey; Andrew N. Radford; Amelia Rose; Giorgio Casiraghi; Natalie Lubbock; Emma Weschke; Benjamin M. Titus; Dan A. Exton; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recreational SCUBA diving is widespread and increasing on coral reefs worldwide. Standard open-circuit SCUBA equipment is inherently noisy and, by seeking out areas of high biodiversity, divers inadvertently expose reef communities to an intrusive source of anthropogenic noise. Currently, little is known about SCUBA noise as an acoustic stressor, and there is a general lack of empirical evidence on community-level impacts of anthropogenic noise on coral reefs. Here, we conducted a playback experiment on Caribbean reefs to investigate impacts of SCUBA noise on fish communities and interspecific cooperation at ecologically important cleaning stations of the Pederson’s cleaner shrimp Ancylomenes pedersoni . When exposed to SCUBA-noise playback, the total occurrence of fishes at the cleaning stations decreased by 7%, and the community and cleaning clientele compositions were significantly altered, with 27% and 25% of monitored species being affected, respectively. Compared with ambient-sound playback, SCUBA-noise playback resulted in clients having to wait 29% longer for cleaning initiation and receiving 43% less cleaning; however, cheating, signalling, posing and time spent cleaning were not affected by SCUBA-noise playback. Our study is the first to demonstrate experimentally that SCUBA noise can have at least some negative impacts on reef organisms, confirming it as an ecologically relevant pollutant. Moreover, by establishing acoustic disturbance as a likely mechanism for known impacts of diver presence on reef animals, we also identify a potential avenue for mitigation in these valuable ecosystems.

Co‐occurrence of herbivorous fish functional groups correlates with enhanced coral reef benthic state - Catherine E. Sheppard; Gareth J. Williams; Dan A. Exton; Sally A. Keith (Global Ecology and Biogeography, 2023)
Aim Biodiversity loss is impacting essential ecosystem functions and services across the globe. Recently, our interest in the benefits of biodiversity for ecosystem function has shifted focus from measurements of species richness to functional diversity and composition. However, the additional importance of other community characteristics, such as species evenness and co‐occurrence, for diversity‐driven ecosystem function is less known. We used herbivorous coral reef fish as a model system to investigate how co‐occurrence of different functional groups, rather than purely functional diversity, within an assemblage might affect the coral reef benthic state. Location Western Atlantic. Time period 2007–2017. Major taxa studied Herbivorous reef fish. Methods We analysed benthic and fish assemblage data from 601 sites across 12 countries in the western Atlantic. Using diversity–interaction models, we investigated how the composition and relative abundances of reef fish functional groups were correlated with benthic cover and estimates of coral calcification rates. We used statistical interactions to explore the importance of co‐occurrence of herbivorous fish functional groups for the coral reef benthic state. Results We found that co‐occurrence of herbivorous fish functional groups, in addition to functional diversity, was correlated with reduced algal cover and increased coral accretion. Moreover, pairwise statistical interactions between functional groups were significantly correlated with an improvement in the coral reef benthic state. Main conclusions Our results support the idea that functional group co‐occurrence, in addition to functional diversity, within herbivorous fish offers additional benefits to the coral reef benthic state. We identify farming damselfish and excavating parrotfish as potential key determinants of the coral reef benthic state and highlight that co‐occurrence of cropping and scraping herbivores might promote coral accretion. Our findings support the argument that protecting herbivore abundance without regard to the species and functional groups present is not enough to preserve coral reef health and that fine‐scale community composition must be considered.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Light‐driven dynamics between calcification and production in functionally diverse coral reef calcifiers - Jennifer Mallon; Tyler Cyronak; Emily R. Hall; Anastazia T. Banaszak; Dan A. Exton; Adrian M. Bass (Limnology and Oceanography, 2022)
Coral reef metabolism underpins ecosystem function and is defined by the processes of photosynthesis, respiration, calcification, and calcium carbonate dissolution. However, the relationships between these physiological processes at the organismal level and their interactions with light remain unclear. We examined metabolic rates across a range of photosynthesising calcifiers in the Caribbean: the scleractinian corals Acropora cervicornis , Orbicella faveolata , Porites astreoides , and Siderastrea siderea , and crustose coralline algae (CCA) under varying natural light conditions. Net photosynthesis and calcification showed a parabolic response to light across all species, with differences among massive corals, branching corals, and CCA that reflect their relative functional roles on the reef. At night, all organisms were net respiring, and most were net calcifying, although some incubations demonstrated instances of net calcium carbonate (CaCO 3 ) dissolution. Peak metabolic rates at light‐saturation (maximum photosynthesis and calcification) and average dark rates (respiration and dark calcification) were positively correlated across species. Interspecies relationships among photosynthesis, respiration, and calcification indicate that calcification rates are linked to energy production at the organismal level in calcifying reef organisms. The species‐specific ratios of net calcification to photosynthesis varied with light over a diurnal cycle. The dynamic nature of calcification/photosynthesis ratios over a diurnal cycle questions the use of this metric as an indicator for reef function and health at the ecosystem scale unless temporal variability is accounted for, and a new metric is proposed. The complex light‐driven dynamics of metabolic processes in coral reef organisms indicate that a more comprehensive understanding of reef metabolism is needed for predicting the future impacts of global change.

Large-scale invasion of western Atlantic mesophotic reefs by lionfish potentially undermines culling-based management - Dominic A. Andradi-Brown; Mark J. A. Vermeij; Marc Slattery; Michael Lesser; Ivonne Bejarano; Richard Appeldoorn; Gretchen Goodbody-Gringley; Alex D. Chequer; Joanna M. Pitt; Corey Eddy; Struan R. Smith; Eran Brokovich; et al. (Biological Invasions, 2017)

Using an isolated population boom to explore barriers to recovery in the keystone Caribbean coral reef herbivore Diadema antillarum - Max D. V. Bodmer; Alex D. Rogers; Martin R. Speight; Natalie Lubbock; Dan A. Exton (Coral Reefs, 2015)

Temporal patterns of Pederson shrimp (Ancylomenes pedersoni Chace 1958) cleaning interactions on Caribbean coral reefs - Benjamin M. Titus; Marymegan Daly; Dan A. Exton (Marine Biology, 2015)

Uncovering the volatile nature of tropical coastal marine ecosystems in a changing world - Dan A. Exton; Terry J. McGenity; Michael Steinke; David J. Smith; David J. Suggett (Global Change Biology, 2015)
Biogenic volatile organic compounds ( BVOC s), in particular dimethyl sulphide ( DMS ) and isoprene, have fundamental ecological, physiological and climatic roles. Our current understanding of these roles is almost exclusively established from terrestrial or oceanic environments but signifies a potentially major, but largely unknown, role for BVOC s in tropical coastal marine ecosystems. The tropical coast is a transition zone between the land and ocean, characterized by highly productive and biodiverse coral reefs, seagrass beds and mangroves, which house primary producers that are amongst the greatest emitters of BVOC s on the planet. Here, we synthesize our existing understanding of BVOC emissions to produce a novel conceptual framework of the tropical marine coast as a continuum from DMS ‐dominated reef producers to isoprene‐dominated mangroves. We use existing and previously unpublished data to consider how current environmental conditions shape BVOC production across the tropical coastal continuum, and in turn how BVOC s can regulate environmental stress tolerance or species interactions via infochemical networks. We use this as a framework to discuss how existing predictions of future tropical coastal BVOC emissions, and the roles they play, are effectively restricted to present day ‘baseline’ trends of BVOC production across species and environmental conditions; as such, there remains a critical need to focus research efforts on BVOC responses to rapidly accelerating anthropogenic impacts at local and regional scales. We highlight the complete lack of current knowledge required to understand the future ecological functioning of these important systems, and to predict whether feedback mechanisms are likely to regulate or exacerbate current climate change scenarios through environmentally and ecologically mediated changes to BVOC budgets at the ecosystem level.